Comparative Study Of Anthropometric And Basic Hysiological Parameters Of Female Children Of Pre-Pubertal, Pubertal And Post-Pubertal Age Groups From Two Districts Of West Bengal, India - ARPITA GHOSH; RUDRANI MUKHERJEE; DEBOSREE GHOSH (International Journal of Pharma and Bio Sciences, 2015)
Any variations in the anthropometric parameters i.e., height, body mass, BMI, BSA, body fat %, WHR, WHtR etc., and basic physiological parameters i.e., haemoglobin content, respiratory rate, pulse rate, blood pressure etc., in female school children of pre-pubertal, pubertal and post-pubertal age groups from Bankura District and from the district of West Midnapore of West Bengal, India were studied. We also evaluated if there is any significant difference in the various anthropometric and physiological parameters studied in the children of the three different age groups from the two different districts of the state of West Bengal. We observed significant variations in the anthropometric and physiological parameters in the three different age groups of female children of the two districts and also some significant differences were observed between the respective age groups from the two districts. Variations in anthropometric parameters of children bear a direct relationship with possible health risks, growth pattern and socio economic status of the community from which the children belong. Besides, assessment of anthropometric parameters and basic physiological parameters in school children helps us to predict possible suitable physiological predomination for selection of individuals for training of specific types of sports. Above all, the studies helped us to predict the phylogenetic relationship, if any, between the two different communities residing in two different districts of the state of West Bengal India. Besides, the study revealed possible vulnerability of the children to health ailments which may be because of lifestyle and socioeconomic status of those children.